Assessing Seminal Plasma Malondialdehyde Acid as a Diagnostic Tool for Male Infertility: A Case-Control Study - Kumar, Naina; Deepthi, KN; Padugupati, Suhasini; Ghose, Seetesh (Reviews on Recent Clinical Trials, 2025)
AimThe aim of this study was to assess the role of seminal Malondialdehyde Acid (MDA) in the diagnosis of male infertility.BackgroundBoth male and female infertility is increasing all over the world.ObjectiveThe purpose of this study was to assess the impact of seminal MDA levels on various semen parameters of healthy fertile men and men with infertility, and to know the efficacy of seminal MDA in the diagnosis of male infertility.MethodsThis case-control study was carried out at the Department of Obstetrics and Gynaecology of a tertiary care center in rural Southern India over a period of two years. The study included 90 infertile men (≥21-50 years) having some pathology in semen reports as cases and 90 fertile men (having biological children) with normal semen reports as controls. Biochemical tests for MDA were performed using Human MDA Assay kits on 180 cryopreserved semen samples following the standard protocol. Results of seminal MDA levels were assessed among cases and controls and correlated with different semen parameters.ResultsThe mean±SD age for cases was 30.10 ± 4.75 years, and for controls, it was 29.79 ± 5.08 years. Of all the cases, 44 (48.9%) had asthenozoospermia, 22 (24.4%) had oligoasthenozoospermia, 14(15.6%) had oligozoospermia, and 10 (11.1%) had azoospermia. A statistically substantial variance was observed in mean values of MDA (1.03 ± 0.31 mmol/mL vs. 0.60 ± 0.14 mmol/mL; p =0.001) between fertile men and men with abnormal semen reports. A negative association was observed between semen MDA levels with sperm motility, concentration, and normal morphology in 180 participants. The sensitivity of MDA for male infertility prediction was 86.67% at 76.67% specificity, 78.79% positive predictive value, and 78.79% negative predictive value.ConclusionMDA has been found to be a promising biomarker for predicting male infertility. However, large sample sizes and prospective cohort studies are required to further confirm its predictive accuracy across various populations.
Keywords: semen